Rare complication of a common obesity procedure. (26th February 2016) - Ereifej, Lisa K; Crowell, Richard; Schade, David
Abstract : Laparoscopic gastric banding has been widely used to treat obesity. Aspiration pneumonia has not been reported as a complication of bariatric surgery. We present a patient who had bariatric surgery and presented with aspiration pneumonia. A 64-year-old woman with a medical history of obesity and laparoscopic gastric banding presented to urgent care with 1 month of dry, continuous cough. A chest CT scan demonstrated a large opacity in the left upper lobe peripherally containing an air bronchogram, and the oesophagus was significantly enlarged and fluid filled. The patient was diagnosed with aspiration pneumonia. She received antibiotics and the gastric band was deflated. A repeat CT scan showed resolution of the pneumonia. To our knowledge, aspiration pneumonia is an unreported complication of gastric banding. Not recognising this complication may cause delay in the correct diagnosis and leads to invasive procedures with increased morbidity.